Everyday Law in Russia - Hendley, Kathryn (Book collections on Project MUSE., 2017)
This text challenges the prevailing common wisdom that Russians cannot rely on their law and that Russian courts are hopelessly politicized and corrupt. While acknowledging the persistence of verdicts dictated by the Kremlin in politically charged cases, the text explores how ordinary Russian citizens experience law.